Analyzing the Impact of Airport Train Accessibility and Self-Service Check-In System at Soekarno-Hatta International Airport - Fasyah Maulana Halim; Jonathan Tri Kuncoro; Indra Yuzal; Jana Sandra (Whoosh: Journal of Transportation and Logistic, 2026)
Soekarno-Hatta International Airport plays a significant role in supporting the tourism industry and national connectivity. Beyond aircraft, the Airport Railway also serves as a critical facilitator of passenger mobility. This research aims to assess passenger satisfaction concerning Railink services and airport facilities, such as self-service check-in (SSCI). The primary objective of this study is to measure the accessibility of the Airport Train and the utilization of SSCI, as well as their impact on customer satisfaction. This research adopts a quantitative approach, utilizing questionnaires collected from 100 respondents from Soekarno-Hatta Airport facility users. The data collected have been subjected to analysis employing the SPSS method, using a multiple linear regression model to examine the influence of the aforementioned variables on customer satisfaction. the result of airport train accesibility (X1) and self check-in facilities (X2) positively impact 63% of the observed variability in user satisfaction.